THE DAYTON CONCEPT OF PERFORMING LEGISLATIVE AND OTHER FUNCTIONS OF THE PARLIAMENTARY ASSEMBLY OF BOSNIA AND HERZEGOVINA: COLLAPSE OF THE RULE OF LAW AND EFFECTIVE POLITICAL DEMOCRACY (EU and comparative law issues and challenges series (ECLIC), 2024)
Bosnia and Herzegovina is a State whose current constitutional solutions are not the result of an effort to ensure basic democratic principles regarding the way of election and functioning of the institutions of the system, but are the result of an effort to establish and ensure peace through the Peace Agreements. However, today - almost thirty years after the entry into force of the General Framework Agreement for Peace in Bosnia and Herzegovina, such constitutional solutions have proven to be an insurmountable obstacle to, in the first place, the realization of the rule of law and development of effective political democracy, that is, to the fulfillment of the necessary conditions on the path to European integration. The constitutional system of Bosnia and Herzegovina, as it is well known, is interwoven with norms of a discriminatory nature that are not in accordance with the European Convention and its protocols, which has resulted in several judgments of the European Court of Human Rights in Strasbourg. It is a matter of severe discrimination on an ethnic basis in domain of the electoral rights of citizens, which is visible at first glance. Maintaining such a state of affairs and not implementing the judgments of the European Court of Human Rights, despite the fact that Bosnia and Herzegovina has ratified the European Convention - and especially its Protocol 12 - along with other ratified protocols, as well as the fact that according to the Constitution of Bosnia and Herzegovina, the above mentioned instruments are the part of the legal system of Bosnia and Herzegovina Herzegovina, represents an insurmountable obstacle for the serious approach to fulfilling other conditions from the European integration process. In this place, it comes to the unequal value of the votes and discrimination within the decision-making process in the Parliamentary Assembly of Bosnia and Herzegovina (which is not visible at first glance) and - in the first place, through the so-called entity voting in both Houses of this representative body (House of Representatives and House of Peoples). Thanks to the Dayton constitutional solutions that produce a multiple inequality of the value of votes of MPs of the House of Representatives and delegates of the House of Peoples of the Parliamentary Assembly of Bosnia and Herzegovina, along with other deviations, any serious approach to fulfilling the conditions of the European integration process is impossible, the violation of the rule of law has become a constant phenomenon, and all this it has a very harmful effect on the principle of effective political democracy to the point of its complete cancellation. This paper contains considerations regarding the procedures of execution the functions of the Parliamentary Assembly of Bosnia and Herzegovina, along with an analysis of the key causes of delays in fulfilling the conditions of the European integration process based on valid norms that produce an unequal value of the votes in the decision-making process of the Parliamentary Assembly of Bosnia and Herzegovina, but also in terms of violations generally accepted democratic standards of a legal nature that refer to the election of the Houses of this representative body, their mutual relationship and overall position. Due to the multiple inequality of vote and discrimination in the decision-making process of the House of Representatives of the Parliamentary Assembly of BH - as a directly elected House, and in relation to the delegates of the indirectly elected House of Peoples, proceeding has been initiated before the European Court of Human Rights in 2021 (case no. 34891/21), and a decision is expected in this case.